Hypnosis and Dyspareunia: A Meta Analysis - Kumalasari, Ratna Dewi; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Sexual satisfaction refers to a person's pleasant feelings from the type of sexual relationship that forms an important part of one partner's impression of another. 75% of women experience sexual problems. Symptoms of sexual dysfunction occur in nearly half of the marriage period and 75% of couples need therapy. This study aims to analyze the effect of hypnosis on pain during sexual activity and the intensity of pain.Subjects and Method: This study was a meta-analysis and a systematic study. The articles used were obtained from several electronic databases including Pubmed, Science Direct, Springer Link, and Google Scholar. Articles were collected for 4 weeks. The keywords to search for articles were as follows: